Female specific problems in Indian gymnasts - Sharma, R.; Kumar Nigam, A. (International Journal of Health Sciences & Research, 2015)
Aim was to study the female specific problems in national level female gymnasts, which signifies the prevalence of menstrual disorders and related problems in Indian elite female gymnasts. A total number of 32 female gymnasts of national level, who secured first three positions in apparatus and team event finals, were investigated in an independent group design. The selection of females was done randomly to minimize the source of error. The age of the gymnasts was 14+ years. A pre-tested semi-structured questionnaire was used for the purpose of data collection. The questionnaire was prepared taking consideration about information related to menstruation and associated problems faced by Indian female gymnasts. Each question was explained in detail to the athletes. Copies of the questionnaire were distributed to thirty two female gymnasts randomly. As soon as a group of players completed the questionnaire, it was collected from the gymnasts and verified that no questionnaire was left without being answered. The results showed a high incidence of delayed menarche. 78.13 percent females had menstrual problems and 65.63 percent of them believed that menstruation affected their performance. Menstrual problem was felt in most of the females (40. 63 percent) during off-season. Anger was the commonest mood swing experienced (34.37 percent). Most of the female gymnasts suffered from increased fatigue onset of menses (62.50 percent) and during the course of menses (87.50 percent). Menorrhea was felt the most i.e. 65.62 percent and most of the females (50.00 percent) suffered from back pain during menses. Most of the females (53.13 percent) experienced the joint pain and pulse rate increased 3-4 days before onset of menses. The results of the study revealed that no doubt, female gymnasts of today are stronger and faster than ever, but existence of some medical problems specific to them cannot be denied. These problems are delayed menarche, increased fatigue, mood swing, increased pulse rate, pre-menstruation tension, dysmenorrhea and menorrhea etc. The study explains the desperate need to educate the coaches and female athletes on menstrual disorders and their related physical, psychological and physiological problems in female gymnasts.